COGNITIVE DISSONANCE THEORY IN HA HA BILLIARD MANADO - Mamesah, Aprilya (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Marketer that can win consumers’ heart will survive in the business competition because the duty of marketing is not just how to get more consumer but how to require and retain the loyal consumer. However cognitive dissonance also is a part of consumers’ mindset. It is crusial for marketer to learn more about this theory. Through the dissonance feeling, marketer will know the real perception of consumer towards their product or service. Therefore, an effetive marketing strategy approach could enable companies or organizations to build stronger customer relationship as well as imprvin their sales performance and profitability. This research uses qualitative research and case study analysis. The research objective is how cognitive dissonance affecting consumer buying decision in Ha Ha Billiard Manado. The informant or participant of this research consist of ten consumer of this particular business and divided into five adult informants and five as college student informants. Results and conclusions are Beliefs, Religious Value, Custom, Politeness, Family Status, Emotional Reaction, Word of Mouth and Peer Group are the factors that can make consumer feel dissonance to go to Ha Ha Billiard or to spent more time in this place; law is not a factor that make consumer feel dissonance to go to this particular business and to stay longer in that place. There are several consumer that still pay attention, even hold tightly the rules of eastern culture, because the factors such as custom, religious value, politeness, family status that related with eastern culture can create dissonance towards most informants in this research. Keywords: cognitive dissonance